Effect of empagliflozin on cardiac remodelling in South Asian and non-South Asian individuals: insights from the EMPA-HEART CardioLink-6 randomised clinical trial - William Barbour; Erika Wolff; Pankaj Puar; Makoto Hibino; Ehab Bakbak; Aishwarya Krishnaraj; Raj Verma; Meena Verma; Adrian Quan; Andrew T. Yan; Kim A. Connelly; Hwee Teoh; et al. (BMC Cardiovascular Disorders, 2023)
Abstract Background This exploratory sub-analysis of the EMPA-HEART CardioLink-6 trial examined whether the previously reported benefit of the sodium-glucose cotransporter 2 (SGLT2) inhibitor empagliflozin on left ventricular (LV) mass (LVM) regression differs between individuals of South Asian and non-South Asian ethnicity. Methods EMPA-HEART CardioLink-6 was a double-blind, placebo-controlled clinical trial that randomised 97 individuals with type 2 diabetes mellitus (T2DM) and coronary artery disease (CAD) to either empagliflozin 10 mg daily or placebo for 6 months. LV parameters and function were assessed using cardiac magnetic resonance imaging. The 6-month changes in LVM and LV volumes, all indexed to baseline body surface area, for South Asian participants were compared to those for non-South Asian individuals. Results Compared to the non-South Asian group, the South Asian sub-cohort comprised more males, was younger and had a lower median body mass index. The adjusted difference for LVMi change over 6 months was -4.3 g/m2 (95% confidence interval [CI], -7.5, -1.0; P = 0.042) for the South Asian group and -2.3 g/m2 (95% CI, -6.4, 1.9; P = 0.28) for the non-South Asian group (Pinteraction = 0.45). There was no between-group difference for the adjusted differences in baseline body surface area-indexed LV volumes and LV ejection fraction. Conclusions There was no meaningful difference in empagliflozin-associated LVM regression between South Asian and non-South Asian individuals living with T2DM and CAD in the EMPA-HEART CardioLink-6 trial. Trial registration ClinicalTrials.gov Identifier: NCT02998970 (First posted on 21/12/ 2016).